Analytical Study of the Thermal Activation of Tb Doped Amorphous SiC:H Thin Films - Guerra Torres, J.A.; Tucto, K.; Montañez, L.M.; De Zela, F.; Töfflinger, J.A.; Winnacker, A.; Weingärtner, R. (Materials Research Society, 2016)
The luminescence of Tb-doped a-SiC:H thin films with different Tb concentrations under sub-bandgap photon excitation was investigated. Two independent processes were identified. The annealing induced activation of the Tb3+ and the inhibition of host-mediated non-radiative recombination paths. The integrated emission intensity is described by a rate equation model, considering these two. In this study, the luminescence enhancement with increasing annealing temperature is shown. The optimal Tb concentration and annealing temperature for the highest Tb-related light emission intensity is determined. Finally, a parameter proportional to the number of optically active ions is found through the aforementioned model.
Keywords: Materials science; Luminescence; Annealing (glass); Doping; Amorphous solid; Thin film; Radiative transfer; Excitation; Ion; Emission intensity; Optoelectronics; Band gap; Analytical Chemistry (journal); Nanotechnology; Optics; Composite material; Crystallography; https://purl.org/pe-repo/ocde/ford#1.03.06